Chelation versus Non‐Chelation Control in the Stereoselective Alkenyl sp2 C−H Bond Functionalization Reaction. Issue 18 (30th March 2017) - Liang, Qiu‐Ju; Yang, Chao; Meng, Fei‐Fan; Jiang, Bing; Xu, Yun‐He; Loh, Teck‐Peng
Abstract: A hydroxy group chelation‐assisted stereospecific oxidative cross‐coupling reaction between alkenes was developed under mild reaction conditions. In the presence of palladium catalyst, the alkenes tethered with hydroxy functionality can couple efficiently with electron‐deficient alkenes to form the corresponding multi‐substituted olefin products. The hydroxy group on the substrate could play dual roles in reaction, acting as the directing group for alkenyl C−H bond activation and controlling the stereoselectivity of the products. Abstract : Stereospecific oxidative cross‐coupling between alkenes assisted by hydroxy group chelation was developed. In the presence of palladium catalyst, alkenes tethered by the hydroxy functionality can couple with electron‐deficient alkenes to form olefin products. The hydroxy group acts as both directing group for alkenyl C−H bond activation and stereoselectivity control.